Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/plants7030070
|View full text |Cite
|
Sign up to set email alerts
|

Plants of Genus Mentha: From Farm to Food Factory

Abstract: Genus Mentha, a member of Lamiaceae family, encompasses a series of species used on an industrial scale and with a well-described and developed culture process. Extracts of this genus are traditionally used as foods and are highly valued due to the presence of significant amounts of antioxidant phenolic compounds. Many essential oil chemotypes show distinct aromatic flavor conferred by different terpene proportions. Mint extracts and their derived essential oils exert notable effects against a broad spectrum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 167 publications
1
95
0
Order By: Relevance
“…Also, in view of the environmental, food-safety and health related issues associated with the application of chemical insecticides, growing emphasis is being laid on pest control through plant resources. In addition to the menthol and pulegone present in the essential oil of the Mentha species, which are the substances that give mints their characteristic aromas and flavors [4,110,111], they are also found to possess insecticidal, antiviral and fungicidal activities. Pulegone showed potent insecticidal activity against the mushroom scatopsid fly, Scatopse spp., in fumigant bioassay [112], and significant antibacterial activity is also observed for Mentha oil due to the presence of menthol [113].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in view of the environmental, food-safety and health related issues associated with the application of chemical insecticides, growing emphasis is being laid on pest control through plant resources. In addition to the menthol and pulegone present in the essential oil of the Mentha species, which are the substances that give mints their characteristic aromas and flavors [4,110,111], they are also found to possess insecticidal, antiviral and fungicidal activities. Pulegone showed potent insecticidal activity against the mushroom scatopsid fly, Scatopse spp., in fumigant bioassay [112], and significant antibacterial activity is also observed for Mentha oil due to the presence of menthol [113].…”
Section: Discussionmentioning
confidence: 99%
“…TMS has also showed efficacy in promoting clinical recovery after stroke and NDDs, the latter including vascular and post-stroke dementias, but this applicability is still in its infancy [1,8]. Other non-pharmacological approaches, for example, Shiatsu, physical activity, music therapy, have also showed beneficial effects for Quality of Life (QoL) in patients with several types of dementia [9,10]. The undesirable side-effects associated with some pharmacological compounds, used in conventional medicine, support the relevance of creating alternative therapies with higher efficacy and bioavailability, and fewer side-effects [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Man's reliance on nature for treating illness predates recorded history, and the plant kingdom is one of the most important sources of medicines [3][4][5][6][7][8][9]. The medicinal properties of plants are mostly ascribed to secondary phytochemical metabolites [10].…”
Section: Introductionmentioning
confidence: 99%
“…Peppermint (Mentha x piperita L.), a natural hybrid of Mentha aquatica L. and Mentha spicata L., is cultivated broadly in the world. It is a valuable species due to production of essential oil (EO), applied in different industries [1,2]. In vitro studies showed, that peppermint EO displays also significant allelopathic and phytotoxic potential, by inhibiting germination and early growth of various weeds [3].…”
Section: Introductionmentioning
confidence: 99%